Assessment of patient satisfaction in public hospitals in Cyprus: A descriptive study - Merkouris, Anastasios; Andreadou, Angeliki; Athini, Evdokia; Hatzimbalasi, Maria; Rovithis, Michalis (My University, 2013)
questionnaire and the sample consisted of a random sample of 324 patients from 5 public hospitals in Cyprus with at least 3 days of hospitalisation. Results: The sample consisted of 159 medical (49.1%) and 165 surgical patients (50.9%), the majority of the sample were male (200 - 61.7%) and the mean age was 57.6 years (SD=17.8 years). Overall, patients showed enthusiasm with the medical care provided (Mean=3.97, SD=0.65, R=1- 5). Particularly, patients were more satisfied with the technical aspect of care (Mean=4.20, SD=0.62) and less satisfied with the provision of information (Mean=3.71, SD=0.92) and hospitalisation (Mean=3.84, SD=0.70) and most particularly with food and resting time. There was no statistically significant difference in relation to the department (medical or surgical), sex, age, educational level and residency. Conclusions: Nurses need to show greater amount of interest to the information-giving process and the autonomy of the patients. Additionally, an effort should be made to improve hospitalisation services. Evaluating patients' satisfaction should be constant so as to reformulate the baseline and to be able to assess interventions and changes in nursing care provision. Introduction: Patient satisfaction has become an established outcome indicator of the quality and the efficiency of the health care systems. Patient satisfaction with nursing is considered the most important factor in the moulding of the overall patient satisfaction with hospital services. Aim of the study: To assess medical and surgical patient satisfaction with nursing care in the public hospitals of Cyprus and explore its possible correlation with background factors. Methods: An exploratory, descriptive design, with face-to-face semi-structured interview was employed. Data were collected by using MPSS.
Keywords: Assessment; Patient satisfaction; Nursing care; Hospital